Using MVVM Light with your Xamarin Apps - Johnson, Paul (Apress, 2018)
Learn how to use the popular MVVM Light development framework with a focus on reliable, maintainable code that can be deployed across any of the .NET-supported mobile platforms. Clear examples are provided of the advantages of the MVVM platform along with step-by-step demonstrations of how to create applications at different levels of complexity. Application development is covered for iOS, Android, and Windows phone (UWP) using MVVM Light as the central framework. The model-view-view-model (MVVM) pattern is valued by many developers as an excellent way to create sophisticated modern applications. Its clear separation of presentation and business logic produces a clean implementation that promotes speed, scalability, and code reuse in applications with a complex UI. These characteristics have long been highly valued by WPF developers, and now that benefit is available to Xamarin developers, too. What You'll Learn: Set up and install MVVM Light Understand the advantages and disadvantages of MVVM Discover why inversion of control is important in MVVM Conduct unit testing of MVVM apps Convert your existing apps to use MVVM Use MVVM Light within a Xamarin Forms app Use webservices Be introduced to the new .NET 2.0 Standard Class Library and how to use MVVM Light with it.